Indocyanine green tissue angiography affects anastomotic leakage after esophagectomy: a retrospective, case-control study - Karampinis, Ioannis; Ronellenfitsch, Ulrich; Mertens, Christina; Gerken, Andreas; Hetjens, Svetlana; Post, Stefan; Kienle, Peter; Nowak, Kai (International journal of surgery, 2017)
Purpose: Optimal perfusion of the gastric conduit during esophagectomy is elementary for the anastomotic healing since poor perfusion has been associated with increased morbidity due to anastomotic leaks. Until recently surgical experience was the main tool to assess the perfusion of the anastomosis. We hypothesized that anastomoses located in the zone of optimal ICG perfusion of the gastric conduit (“optizone”) have a reduced anastomotic leakage rate after esophagectomy. Methods: Indocyanine green (ICG) fluorescence tissue angiography was used to evaluate the anastomotic perfusion in 35 patients undergoing esophagectomy with gastric conduit reconstruction. The transition point of the “optizone” to the malperfused area of the conduit was defined macroscopically and with the use of ICG angiography during the operation. The anastomosis was performed in the optizone whenever possible. The results of the ICG patients were retrospectively reviewed and compared with 55 patients previously operated without ICG angiography. Results: The visual assessment of the conduit perfusion concurred with the ICG angiography in 27 cases. In 8 cases (22.8%) the ICG angiography deviated from the visual aspect. One case of anastomotic leakage was observed in the group of patients in which the anastomosis could be performed in the optizone (1/33; 3%) compared with 10 cases in the control group (18%; p = 0.04). In two cases we had to perform the anastomosis in an area of compromised ICG perfusion. Both patients developed an anastomotic leakage. Conclusions: ICG tissue angiography represents a feasible and reliable technical support in the evaluation of the anastomotic perfusion after esophagectomy. In this retrospective analysis we observed a significant decrease in anastomotic leakage rate when the anastomosis could be placed in the zone of good perfusion defined by ICG fluorescence. A prospective trial is needed in order to provide higher level evidence for the use of ICG fluorescence in reducing leakage rates after esophagectomy.
Available online 13 November 2017
Gesehen am 05.06.2018